2017
DOI: 10.1038/s41598-017-10982-y
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical stability and transfection efficiency of cationic amphiphilic copolymer/pDNA polyplexes for spinal cord injury repair

Abstract: Multiple age-related and injury-induced characteristics of the adult central nervous system (CNS) pose barriers to axonal regeneration and functional recovery following injury. In situ gene therapy is a promising approach to address the limited availability of growth-promoting biomolecules at CNS injury sites. The ultimate goal of our work is to develop, a cationic amphiphilic copolymer for simultaneous delivery of drug and therapeutic nucleic acids to promote axonal regeneration and plasticity after spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…We also observed that PgP can efficiently protect pDNA from nucleases in serum for up to 24 h, whereas pDNA without PgP was completely degraded by serum nucleases within 3 h. These results show that PgP may be a promising non-viral gene carrier for systemic gene therapy in vivo . In the long-term storage stability study, we observed that the transfection efficiency of PgP/pGFP polyplexes in C6 (rat glioma) cells was maintained up to four months at 4 °C and this result is consistent with the long term stability of PgP/pGFP and PgP/siRhoA observed in B35 (neuroblastoma) cells in our laboratory [21,24]. This demonstrates that PgP can form a stable complex with both pDNA and siRNA and preserve the bioactivity of nucleic acids during long-term storage, an important challenge for the clinical translation of non-viral vectors.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We also observed that PgP can efficiently protect pDNA from nucleases in serum for up to 24 h, whereas pDNA without PgP was completely degraded by serum nucleases within 3 h. These results show that PgP may be a promising non-viral gene carrier for systemic gene therapy in vivo . In the long-term storage stability study, we observed that the transfection efficiency of PgP/pGFP polyplexes in C6 (rat glioma) cells was maintained up to four months at 4 °C and this result is consistent with the long term stability of PgP/pGFP and PgP/siRhoA observed in B35 (neuroblastoma) cells in our laboratory [21,24]. This demonstrates that PgP can form a stable complex with both pDNA and siRNA and preserve the bioactivity of nucleic acids during long-term storage, an important challenge for the clinical translation of non-viral vectors.…”
Section: Discussionsupporting
confidence: 77%
“…A cationic, amphiphilic copolymer, PgP, has been developed by our group and has been shown to perform as an efficient drug and non-viral gene carrier in vitro as well as in in vivo animal models [21,22,24]. As a block copolymer that forms polymeric micelles in aqueous solution with a hydrophobic core and hydrophilic, cationic shell, PgP has the potential to serve as a combinatorial carrier for the simultaneous delivery of hydrophobic drugs and anionic therapeutic nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the hydrophobic alkyl moieties present in the side chains of PSI contributed to the increase of polymer/DNA polyplexes interaction via Van der Waal's interactions/modulation, which have been reported to facilitate interactions between the polymer backbones and DNA in previous studies . Although an efficient gene delivery can be observed in polyplexes with strong pDNA binding via hydrogen bonding, the presence of an alkyl chain can modulate the integrity of polyplexes by hydrophobic interactions, increasing the binding between the polymer and the DNA.…”
Section: Resultssupporting
confidence: 59%
“…To evaluate the binding strength of PSI derivatives and polyplex integrity, heparin displacement assay was performed. In this experiment, the amount of uncomplexed plasmid is accessed once free double‐stranded DNA can be detected after displacement of DNA from polyplexes by different concentrations of heparin using a commonly described method . For bPEI 25, the optimal complexation ratio is N:P 5, and pEGFP‐N3 was displaced by heparin from concentrations above 0.6 IU per sample (Figure S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…SCI is a common central nervous system disorder characterized by destruction or dysfunction of spinal cord caused by trauma or other causes. [42][43][44] SCI can cause a variety of complications that lead to irreversible loss of sensory and motor functions. Recently, the incidence of SCI showed a significant upward trend especially in developing countries, and this is a heavy burden for the patients' family and society.…”
Section: Discussionmentioning
confidence: 99%